2015
DOI: 10.5152/anatoljcardiol.2015.6287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetyl cysteine on renal functions evaluated by blood neutrophil gelatinase-associated lipocalin levels in geriatric patients undergoing coronary artery bypass grafting

Abstract: Objective:Recent conflicting studies on the renal effects of N-acetyl cysteine (NAC) after cardiac surgery have been published. The aim of this study was to evaluate the renal effects of NAC using neutrophil gelatinase-associated lipocalin (NGAL) blood levels in elderly patients undergoing coronary artery bypass grafting (CABG).Methods:This randomized, double-blinded, placebo-controlled study was conducted among geriatric patients (>65 years) scheduled to undergo CABG. A total of 60 consecutive patients were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Among the 29 eligible RCTs, trials took place in a variety of settings (S5 Table) including Turkey [20, 53, 54, 59, 60, 63, 66, 67, 69, 70], Canada [56, 58, 79], United States of America [52, 55], Finland [73, 78], Germany [61], Italy [75], Belgium [57], India [68, 71, 72], South Korea [65, 77], Iran [64, 76], Brazil [74] and Australia [62]. Sample sizes ranged from 18 [57] to 295 [56] participants (S5 Table).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 29 eligible RCTs, trials took place in a variety of settings (S5 Table) including Turkey [20, 53, 54, 59, 60, 63, 66, 67, 69, 70], Canada [56, 58, 79], United States of America [52, 55], Finland [73, 78], Germany [61], Italy [75], Belgium [57], India [68, 71, 72], South Korea [65, 77], Iran [64, 76], Brazil [74] and Australia [62]. Sample sizes ranged from 18 [57] to 295 [56] participants (S5 Table).…”
Section: Resultsmentioning
confidence: 99%
“…According to the anesthetic technique, six trials [20, 59, 66, 69, 76, 78] used total intravenous anesthesia technique (TIVA), with a total of 348 participants, while 15 trials [54, 57, 60, 63, 65, 67, 68, 7075, 77, 79] reported using inhaled anesthetics with a total of 1,203 participants. Eight trials [52, 53, 55, 56, 58, 61, 62, 64] with a total of 936 participants did not report which anesthetic technique was employed (S6 Table).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some recent studies demonstrated that NAC might prevent contrast nephropathy (impairment of renal function). It has anti‐inflammatory and antioxidant effects that could prevent renal dysfunction (Aldemir et al., 2016).…”
Section: Cysteine and Homocysteine As Biomarker Of Various Diseasesmentioning
confidence: 99%